World growing old - Searbrook, Jeremy (New Delhi, 2007)
For the first time in mankind S history, The world S population is ageing. Decade by decade, people are living longer than they ever have before. For rich countries in the West, the problems are obvious-economies rely on youthful populations to provide for.
Keywords: Aging-Economic aspect